Limestone surface weathering cycles as the basis of circular architectural design (ARTEKS : Jurnal Teknik Arsitektur, 2025)
This study explores the process of limestone weathering as the basis of a circular architectural design method. The natural process of limestone weathering enable neutralization of acid rainwater to improve the quality of the environment. By understanding weathering as a beneficial occurrence rather than unfavorable, this paper analyzes application of limestone material weathering for architectural design. The study identifies three different cycles in limestone weathering, such as the carbon cycle, the water cycle and the cycle of plant growth and decomposition. Based on these cycles, the natural arrangement of limestone surface, angle, depth and shape determines the continuous and discontinuous flows of elements; resulting in patterns of surface formation. Alteration of water flows potentially accelerates or slows down the cyclical phases, producing different environmental effects. The study develop architectural programming that neutralizes water for reforestation and recreation through limestone weathering. The design aims to maintain the limestone preserve, adding cultivation of coccolithophore algae into the natural limestone ecosystem. This design creates a circular system of weathering limestone to act as a carbon sink within the environment, regenerating the overall landscape.
Keywords: Circular design; Limestone cycles; Water neutralization; Weathering